Spray-Flame Synthesis (SFS) and Characterization of Li1.3Al0.3−xYxTi1.7(PO4)3 [LA(Y)TP] Solid Electrolytes - Md Yusuf Ali; Hans Orthner; Hartmut Wiggers (Nanomaterials)
Solid-state electrolytes for lithium-ion batteries, which enable a significant increase in storage capacity, are at the forefront of alternative energy storage systems due to their attractive properties such as wide electrochemical stability window, relatively superior contact stability against Li metal, inherently dendrite inhibition, and a wide range of temperature functionality. NASICON-type solid electrolytes are an exciting candidate within ceramic electrolytes due to their high ionic conductivity and low moisture sensitivity, making them a prime candidate for pure oxidic and hybrid ceramic-in-polymer composite electrolytes. Here, we report on producing pure and Y-doped Lithium Aluminum Titanium Phosphate (LATP) nanoparticles by spray-flame synthesis. The as-synthesized samples consist of an amorphous component and anatase-TiO2 crystalline particles. Brief annealing at 750–1000 °C for one hour was sufficient to achieve the desired phase while maintaining the material’s sub-micrometer scale. Rietveld analysis of X-Ray diffraction data demonstrated that the crystal volume increases with Y doping. At the same time, with high Y incorporation, a segregation of the YPO4 phase was observed in addition to the desired LATP phase. Another impurity phase, LiTiOPO4, was observed besides YPO4 and, with higher calcination temperature (1000 °C), the phase fraction for both impurities also increased. The ionic conductivity increased with Y incorporation from 0.1 mS/cm at room temperature in the undoped sample to 0.84 mS/cm in the case of LAY0.1TP, which makes these materials—especially considering the comparatively low sintering temperature—highly interesting for applications in the field of solid-state batteries.